Evaluation of the antihyperalgesic effect of tapentadol in two human evoked pain models – the TapCapMentho pilot trial. (1st September 2016) - Förster, M.; Helfert, S.; Dierschke, R.; Großkopf, M.; Hüllemann, P.; Keller, T.; Baron, R.; Binder, A.
ABSTRACT: Objective : Tapentadol is effective in the treatment of neuropathic and nociceptive pain and in acute and chronic pain conditions; two mechanisms combining opioid µ-receptor agonism and noradrenergic reuptake inhibition underlie its analgesic effect. Research design and methods : With this single-center, placebo-controlled, double-blind, cross-over pilot-study, we investigated the antihyperalgesic effect of a single oral dose of 100 mg immediate-release tapentadol on thermal and mechanical hyperalgesia in two human models (i.e. 0.6 % topical capsaicin and 40% topical menthol) of evoked neuropathic pain signs in healthy volunteers. Results : No significant differences regarding experimentally induced heat or cold and mechanical (pinprick) hyperalgesia, as assessed by quantitative sensory testing, could be observed between a single dose of drug and placebo (thermal pain thresholds p>0.4, mechanical pain sensitivity p>0.1). Only few mild side effects of tapentadol were reported. Conclusions : The discrepancy between pain models using healthy volunteers and drug trials under real acute and chronic pain conditions in patients as well as methodological aspects may have contributed to this result. The impact of these findings questions the general use of pain models as predictors for early decision making during drug development. The study was registered in ClinicalTrials.gov (NCT01615510).